1998
DOI: 10.1002/(sici)1521-4141(199812)28:12<4236::aid-immu4236>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Genetic origin of IgG antibodies cloned by phage display and anti-idiotypic panning from three patients with autoimmune thrombocytopenia

Abstract: The beneficial use of intravenous immunoglobulins (IVIG) in certain groups of patients with autoimmune thrombocytopenic purpura (AITP) has been proven. AITP is a severe disease in children with a still unknown etiology. It is not clear how IVIG functions in this and other autoimmune diseases. To analyze and compare patient-derived monoclonal IgG antibodies that are bound by IVIG in an anti-idiotypic manner, the combinatorial antibody phage display system was applied. From three different patients with AITP, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 48 publications
6
32
1
Order By: Relevance
“…In case of the light chains, all but one were derived from the germ‐line genes 3r9C5/DPL23, DPL16/VL3.1, or 2a2.27A12/DPL11 corresponding to the loci 3r, 3l, and 2a2, respectively. Again, the same light chain germ‐line genes have also been detected most frequently in AITP [14]. However, the light chain origin appears to be of only minor importance for the selection by IVIG, because many Fab‐phages without functional light chains were strongly bound by IVIG, and light chain loci 3l and 2a2 were also observed among 3/8 unpanned clones.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In case of the light chains, all but one were derived from the germ‐line genes 3r9C5/DPL23, DPL16/VL3.1, or 2a2.27A12/DPL11 corresponding to the loci 3r, 3l, and 2a2, respectively. Again, the same light chain germ‐line genes have also been detected most frequently in AITP [14]. However, the light chain origin appears to be of only minor importance for the selection by IVIG, because many Fab‐phages without functional light chains were strongly bound by IVIG, and light chain loci 3l and 2a2 were also observed among 3/8 unpanned clones.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous studies suggested that IVIG bound in an anti‐idiotypic manner to the Fab molecules [14,15]. The method of biopanning with IVIG apparently did not select for original heavy and light chain pairing [14]. Instead, high affinity of IVIG molecules for either antibody chain seemed to result in enrichment of particular Fab‐phages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maybe the observations mentioned above by Kuwana et al offer a unifying concept for the immunopathological processes. Our own results concerning the idiotypic antibody network in ITP showed the key role of anti‐idiotype antibodies (Ab 2) for the downregulation of pathological antibody production 2,3).…”
Section: Introductionmentioning
confidence: 79%
“…Sequencing was done in an automatic sequencer (LI-COR) using the cycle sequencing kit (Amersham Biosciences) and infrared fluorophore (IRD41)-labeled primers. The infrared dye-labeled sequencing primers were PelB and SeqGb for the H chains and OmpA and SeqLb or SeqKb for the L chains (57,63,64 …”
Section: Analysis Of Nucleotide and Amino Acid Sequences Of Ab2-fabmentioning
confidence: 99%